Peluang Mewujudkan Tata Kelola Victim Trust Fund Di Lembaga Perlindungan Saksi Dan Korban (LPSK) Untuk Pemulihan Korban Akibat Tindak Pidana - Herdiansah, Dian (Universitas Musamus, 2025)
The Victim Trust Fund (VTF) is an alternative financing mechanism designed to ensure comprehensive restitution for crime victims, particularly when offenders are unable to fulfill restitution obligations. In Indonesia, although the concept has emerged through the Victim Assistance Fund (DBK) under the Sexual Violence Act (UU TPKS), its scope and implementation remain limited. This paper aims to analyze the regulatory framework and governance of VTF across selected countries and international institutions, while assessing its applicability within the Indonesian legal system. The research employs a qualitative approach using normative-empirical methods through legal literature review, comparative study, and focus group discussions. Findings reveal that countries such as the Netherlands, the United States, Norway, and the Philippines have developed victim compensation schemes supported by both state and non-state sources. Internationally, the ICC and the United Nations implement trust fund models that emphasize non-financial restorative services. This study concludes that Indonesia must strengthen its legal and institutional frameworks to establish a sustainable VTF, either through an endowment fund or pooling fund model, to enhance victims’ access to holistic and continuous recovery services.